2011
DOI: 10.1177/0310057x1103900418
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Predicted and Perceived Pain from Epidural and Spinal Puncture in Patients Undergoing Elective Caesarean Section

Abstract: The intensity of pain expected by patients before an epidural and/or a spinal puncture is uncertain. The main purpose of this study was to identify and compare the intensity of pain predicted and perceived by patients having an epidural and a spinal procedure. After screening for relevant exclusion criteria, 50 women who were undergoing elective caesarean section under combined spinal-epidural anaesthesia (double-segment technique) were enrolled in the study. Infiltration anaesthesia prior to needle insertion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…We also found that patients expected the procedure to be significantly more painful than they subsequently experienced. This is consistent with the findings of previous smaller studies of epidural and spinal anesthesia procedures 5,7,8 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We also found that patients expected the procedure to be significantly more painful than they subsequently experienced. This is consistent with the findings of previous smaller studies of epidural and spinal anesthesia procedures 5,7,8 .…”
Section: Discussionsupporting
confidence: 92%
“…When categorized into pain groups 3,4 , actual pain associated with the procedure was reported as no/mild pain in most patients (58%), moderate pain in 38% of the patients, and severe pain in only 4% of the patients. We showed that the use of procedural medication in our study had only a minor influence on experienced pain, and the observed levels were comparable to those observed for the EDC procedure [5][6][7] . We also found that patients expected the procedure to be significantly more painful than they subsequently experienced.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Terefore, we measured the anticipated pain of the whole procedure of the spinal block, i.e., from the position and local infltration until the application of the block. Tis is in contrast to T. Yano et al who did not apply local anaesthetic infltration for the spinal block and measured only spinal needle pain [11]. However, Mogensen et al applied local anaesthetic infltration before 18 G Tuohy needle insertion and measured pain due to an epidural catheter [12].…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown that the patient's expectation of pain is higher than what they experience in real. Yano et al studied predicted and perceived pain in females undergoing elective CS and found overestimated anticipated pain by patients [ 11 ]. Mogensen et al also found higher expected pain in the epidural procedure [ 12 ].…”
Section: Introductionmentioning
confidence: 99%